TIME SERIES ANALYSIS OF CREDIT FACILITIES OF SELECTED BANKS AND ECONOMIC GROWTH IN NIGERIA (1988-2023) - Maijama’a, Bilkisu; Ibrahim, Ahmed; Suleiman, Hassan; Unekwu, Mary Udehi (International Journal of Allied Research in Economics (IJARE), 2025)
This study investigates a time series analysis of credit facilities provided by banks and their impact on economic growth in Nigeria from 1988 to 2023. Using secondary data on Real Gross Domestic Product (RGDP), Commercial Bank Credit (CBC), Interest Rate (INTR), and Broad Money Supply (M2) sourced from the Central Bank of Nigeria (CBN) statistical bulletin, this study examines the long-run equilibrium relationship (cointegration) among these variables. A multiple regression model is developed, and econometric techniques are employed, including the Augmented Dickey-Fuller (ADF) test, Johansen Co-integration Test, and Error Correction Model (ECM). The findings revealed that although M2 has a significant short-term impact on RGDP, CBC, and INTR exhibit an insignificant effect. The Johansen Co-integration Test confirms a long-term equilibrium relationship among variables, whereas the Granger Causality Test indicates that M2 Granger-causes RGDP. Despite challenges such as autocorrelation and non-normality in residuals, appropriate econometric corrections, including heteroscedasticity and autocorrelation consistency (HAC) methods, were applied to ensure model reliability. This study concludes that a broad money supply (M2) is a crucial driver of economic growth in Nigeria, emphasising the need for effective monetary policy to stimulate sustainable economic development. However, commercial bank credit and interest rates require strategic reforms to enhance their contribution to economic growth. The findings provide valuable insights for policymakers, financial institutions, and stakeholders in addressing the dynamics of credit facilities and economic performance in Nigeria.